Hyaluronic acid modified MPEG-b-PAE block copolymer aqueous micelles for efficient ophthalmic drug delivery of hydrophobic genistein - Li, Cong (Drug Deliv, 2018)
The ophthalmic drug delivery is a challenge in the clinical treatment of ocular diseases. The traditional drug administration usually shows apparent limitations, such as the low bioavailability from the reason of low penetration of the cornea and the short survival time of drug in the eyes. To overcome these shortcomings, we propose an amphiphilic polymer micelle modified with hyaluronic acid (HA) for high efficient ophthalmic delivery of genistein, a widely used hydrophobic drug for treatment of ocular angiogenesis. The MPEG-b-PAE copolymer was synthesized by the Michael addition reaction, and the final drug carrier MPEG-b-PAE-g-HA was obtained by the process of esterification. Then, genistein was packaged in this drug carrier, getting the final micelles with size of about 84.5 nm. The cell viability tests showed that the micelles take no obvious cytotoxicity to the human cornea epithelium cells. The functionalities of drug slow release and cornea penetration ability were demonstrated in a series ex vivo experiments. Further, the vascular inhibition test illustrated that the micelles could significantly inhibit the angiogenesis of human umbilical vein endothelial cells. These results indicate that the constructed polymer has high feasibility to be used as drug carrier in the treatment of ocular diseases.